2017
DOI: 10.3366/word.2017.0108
|View full text |Cite
|
Sign up to set email alerts
|

Phonological properties of word classes and directionality in conversion

Abstract: In the study of the word-formation process of conversion, one particularly difficult task is to determine the directionality of the process, that is, to decide which word represents the base and which the derived word. One possibility to inform this decision that has received only limited attention is to capitalize on word-class-specific phonological properties. This paper empirically investigates this option for English noun-verb conversion by building on recent findings on phonological differences between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 33 publications
(35 reference statements)
0
23
0
1
Order By: Relevance
“…There are in fact further parameters that psycholinguists have looked at, conveniently summarised by Lohmann (2017), which I come back to in section 3.2, below, where I discuss the phonological analysis conducted in the present paper.…”
Section: Previous Scholarshipmentioning
confidence: 99%
See 1 more Smart Citation
“…There are in fact further parameters that psycholinguists have looked at, conveniently summarised by Lohmann (2017), which I come back to in section 3.2, below, where I discuss the phonological analysis conducted in the present paper.…”
Section: Previous Scholarshipmentioning
confidence: 99%
“…(2) Syllabic complexity: Verbs in child-directed speech have been found to contain more complex syllables than nouns by Monaghan et al (2007), who define this as 'the proportion of phonemes in the word that were consonants' (268). Lohmann (2017) operationalises this parameter differently, as 'the average number of phonemes per syllable for each word'. I treat that as a separate parameter (see 3, below), and follow Nasals (parameter 9) are said to be more common in nouns; velars (10), in verbs; coronals (11), in nouns in Monaghan et al's (2005) (19) Initial stress: A number of studies, including Kelly (1996), have reported that disyllabic nouns tend to have initial stress more often than verbs.…”
Section: Data Collectionmentioning
confidence: 99%
“…Each structural frame consists of the combination of Distributional Semantic (DS) (Harris, 1954) and coarse-grained syntactical word category information-specifically function word category, content word category, and from the last one we segregate verb word category. The coarse-grained word category information used in this work has been shown to emerge from phonological constraints in early language acquisition (Shi et al, 2006;Lohmann, 2017). A structural frame used in this approach constitutes the environment for a particular lexical item.…”
Section: Introductionmentioning
confidence: 99%
“…In regards to the emergence of coarse-grained syntactical constraints, phonologically-based implicit-learning mechanisms have been shown to serve as a precursor to later grammar learning in 4-month-old infants (Friederici et al, 2011), in such sense phonology serves the recognition and representation of function words in English-Learning infants (Shi et al, 2006), and in the derivation process between nouns and verbs in English (Lohmann, 2017). Lateral dendrites, on the other hand, receive information from the previous activations in the same cortical patch making the network aware of the sequence of lexical constituents along each sentence (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation